Efficient Replication of Adeno-Associated Virus Type 2 Vectors: a cis-Acting Element outside of the Terminal Repeats and a Minimal Size - Tullis, Gregory E. (American Society for Microbiology, 2000)
Recombinant adeno-associated virus type 2 (AAV2) can be produced in adenovirus-infected cells by cotransfecting a plasmid containing the recombinant AAV2 genome, which is generally comprised of the viral terminal repeats flanking a transgene, together with a second plasmid expressing the AAV2 rep and cap genes. However, recombinant viruses generally replicate inefficiently, often producing 100-fold fewer virus particles per cell than can be obtained after transfection with a plasmid containing a wild-type AAV2 genome. We demonstrate that this defect is due, at least in part, to the presence of a positive-acting cis element between nucleotides 194 and 1882 of AAV2. Recombinant AAV2 genomes lacking this region accumulated 14-fold less double-stranded, monomer-length replicative-form DNA than did wild-type AAV2. In addition, we demonstrate that a minimum genome size of 3.5 kb is required for efficient production of single-stranded viral DNA. Relatively small recombinant genomes (2,992 and 3,445 bp) accumulated three- to eightfold less single-stranded DNA per monomer-length replicative-form DNA molecule than wild-type AAV2. In contrast, recombinant AAV2 with larger genomes (3,555 to 4,712 bp) accumulated similar amounts of single-stranded DNA per monomer-length replicative-form DNA compared to wild-type AAV2. Analysis of two recombinant AAV2 genomes less than 3.5 kb in size indicated that they were deficient in the production of the extended form of monomer-length replicative-form DNA, which is thought to be the immediate precursor to single-stranded AAV2 DNA.